1989
DOI: 10.1143/jjap.28.l325
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Coefficient and Reaction Rate Constant of the SiH3 Radical in Silane Plasma

Abstract: We study the dynamics of a three-dimensional laser bullet propagating inside a nonlinear saturable medium. We show that an increase of the pump parameter destabilizes the bullet and leads to its destruction through oscillations with increasing amplitude. We propose an inhomogeneous and anisotropic external excitation mechanism leading to a stable oscillating bullet. By varying the frequency of the external excitation, a stable quasi-in-phase or quasi-antiphase internal state can be reached.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
23
1

Year Published

1991
1991
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(29 citation statements)
references
References 5 publications
5
23
1
Order By: Relevance
“…The transport coefficients at low pressure for mass, energy, and momentum namely the viscosity 11, thermal conductivity x and diffusivity D respectively, can be computed , SiH in SiH4 [30], SiH3 in Hz [86] and Si in Ar [87] are consistent with the theoretical expression within the experimental precision.…”
Section: Neutral Collisions and Reactionssupporting
confidence: 58%
See 1 more Smart Citation
“…The transport coefficients at low pressure for mass, energy, and momentum namely the viscosity 11, thermal conductivity x and diffusivity D respectively, can be computed , SiH in SiH4 [30], SiH3 in Hz [86] and Si in Ar [87] are consistent with the theoretical expression within the experimental precision.…”
Section: Neutral Collisions and Reactionssupporting
confidence: 58%
“…In fact it is inconsistent with the measured contributions of SiH3 radicals to a-Si:H film growth [86,1001 and with the power dissipation in a SiHd-HZ rf-discharge [50]. It was indeed demonstrated that pyre lysis at the vibrational temperature of SiH4, computed by a proper balancing of vibrational excitation by electrons and hot H atoms and cooling by V --+ RT transfers (see section 3.4), and checked on available experimental results, always remains negligible versus electron impact dissociation.…”
Section: H O M O G E N E O U S P Y R O L Y S I S Of S I L a N E Smentioning
confidence: 64%
“…This yields an excellent fit to the data for k Seff = 2.3 Â 10 À 11 cm 3 /s. This is quite a surprise, because Si decay in a discharge afterglow has yielded a 15Â larger value for this rate coefficient [3,16], and one expects Si to easily insert into an Si-H bond. Umemoto et al [1] also measured Si in HWCVD and noted a major discrepancy with the discharge rate coefficient.…”
Section: Radical Reactionsmentioning
confidence: 99%
“…There have been many radical measurements in silane discharges and HWCVD, and only a representative portion will be cited [1][2][3][4][5][6][7][8][9][10]. Threshold ionization mass spectroscopy has been used by the Atwater group and in the present measurements to detect radicals.…”
Section: Introductionmentioning
confidence: 99%
“…We followed the profile of the SiH3 signal in some detail, and found that the decay curve could be reproduced only when we considered the contributions of both the bimolecular recom bination and the diffision. The former was proportional to the square of the SiR3 concentration, whereas the latter was linearly dependent on the concentration; thus, the two contributions could be separated (63). Because of the diffi�rence in lifetime, the SiH3 radical was an order of magnitude or so more abundant than SiH and SiH 2 .…”
Section: Diagnosis Of the Silane Discharge Plasma With Ir Diode Lasermentioning
confidence: 99%